Carbon Brainprint Case Study: intelligent buildings - Parsons, David J.; Chatterton, Julia C.; Clements-Croome, Derek; Elmualim, Abbas; Darby, Howard; Yearly, Tom; Davies, Gareth J. (Cranfield University, 2011)
It is estimated that non-domestic buildings were responsible for 18% of UK total greenhousegas emissions (582 Mt CO2e/year) in 2010. Of non-domestic building emissions, 34%(36 Mt CO2e/year) was due to lighting, office equipment and catering and 46%(49 Mt CO2e/year) was due to heating. A team consisting of researchers at the University of Reading, the University's FacilitiesManagement Directorate and Newera Controls Ltd. conducted two separate investigations tomeasure and demonstrate the potential for two important and complementary approaches inachieving energy efficiency and greenhouse gas emission reductions in buildings. The firstfocused on influencing user behaviour, in an office building on the main campus. The secondconsidered an interventionist approach in an accommodation block at the Henley BusinessSchool using intelligent monitoring and control systems. To date, the first investigation has demonstrated a 20% saving in lighting, office equipment andcatering energy use, largely through user awareness and behaviour change. The second has indicated that savings in heating energy of the order of 24% can be achievedby enhancement of legacy Building Management Systems (BMS) using a Building EnergyManagement System (BEMS). There is also scope for further savings if the BEMS system isextended to other services such as lighting.
Keywords: carbon footprint; greenhouse gases; climate change; global warming; LCA; universities; research; energy; efficiency; buildings